Changes in peripapillary choroidal thickness in patients with multiple sclerosis. Issue 1 (21st September 2018) - Garcia‐Martin, Elena; Jarauta, Laura; Pablo, Luis E.; Bambo, Maria P.; Ara, Jose R.; Martin, Jesus; Polo, Vicente; Larrosa, Jose M.; Vilades, Elisa; Ramirez, Teresa; Satue, Maria
Abstract: Purpose: To study peripapillary choroidal thickness (PPCT) around the optic disc and establish zones using a new swept source optical coherence tomography (SS‐OCT) device. To evaluate PPCT differences between patients with multiple sclerosis (MS) and age‐ and sex‐matched healthy controls. Methods: A total of 102 healthy subjects and 51 patients with MS were consecutively recruited. Healthy subjects were divided into teaching ( n  = 51, used to establish choroidal zones) and validating ( n  = 51, used to compare measurements with MS patients) populations. An optic disc 6.0 × 6.0‐mm three‐dimensional scan was obtained using SS‐OCT Triton. A 26 × 26 cube‐grid centred on the optic disc was generated automatically to measure PPCT. Four choroidal zones were established and used to compare PPCT between healthy controls and patients with MS. Results: Peripapillary choroidal thickness (PPCT) was significantly thinner in patients in all concentric zones (p ≤ 0.0001): 134.02 ± 16.59  μ m in MS group versus 171.56 ± 12.43  μ m in the control group in zone 2; 182.23 ± 20.52 versus 219.03 ± 17.99  μ m, respectively, in zone 3; and 223.52 ± 10.70 versus 259.99 ± 10.29  μ m, respectively, in zone 4. The choroidal thinning in the MS group tended to decrease as we distanced from the optic nerve head. Peripapillary choroidal thickness (PPCT) had a similar pattern in controls and MS; it was thicker in the superior region, followed by temporal, nasal and inferior regions. Conclusion: Patients with MS showed peripapillary choroidal thinning when compared with healthy subjects in all zones around the optic disc. Peripapillary choroidal tissue shows a concentric pattern, increasing in thickness when increasing the distance from the optic nerve. The new SS‐OCT could be useful for evaluating choroidal thinning in clinical practice.